The Impact of Metacognitive Training on Enhancing Problem-Solving Skills Among Secondary School Students - Hassan Al-Farsi; Emily Carter (PT Mutiara Bustan Ilmu, 2025)
This study investigates the impact of metacognitive training on enhancing problem-solving skills among secondary school students. Employing a quasi-experimental design with pre-test and post-test control groups, the research involved 60 students divided into experimental and control groups. The experimental group participated in an 8-week metacognitive training program focusing on planning, monitoring, and evaluating learning strategies. Data were collected through problem-solving skill tests, the Metacognitive Awareness Inventory, and student reflection journals. The findings revealed a significant improvement in the problem-solving abilities of students who underwent metacognitive training, as indicated by higher post-test scores and increased metacognitive awareness. Qualitative data from reflections and teacher observations further confirmed the development of self-regulated learning behaviors and strategic problem-solving approaches among participants. The results underscore the effectiveness of integrating metacognitive instruction into the curriculum to foster critical thinking and adaptive learning in secondary education.